Rec-8 dimorphism affects longevity, stress resistance and X-chromosome nondisjunction in C. elegans, and replicative lifespan in S. cerevisiae - Ayyadevara, Srinivas; Tazearslan, Çagdas; Alla, Ramani; Jiang, James C.; Jazwinski, S. Michal; Shmookler Reis, Robert J. (Frontiers in Genetics, 2014)
A quantitative trait locus (QTL) in the nematode C. elegans, “lsq4,” was recently implicated by mapping longevity genes. QTLs for lifespan and three stress-resistance traits coincided within a span of <300 kbp, later narrowed to <200 kbp. A single gene in this interval is now shown to modulate all lsq4-associated traits. Full-genome analysis of transcript levels indicates that lsq4 contains a dimorphic gene governing the expression of many sperm-specific genes, suggesting an effect on spermatogenesis. Quantitative analysis of allele-specific transcripts encoded within the lsq4 interval revealed significant, 2- to 15-fold expression differences for 10 of 33 genes. Fourteen “dual-candidate” genes, implicated by both position and expression, were tested for RNA-interference effects on QTL-linked traits. In a strain carrying the shorter-lived allele, knockdown of rec-8 (encoding a meiotic cohesin) reduced its transcripts 4-fold, to a level similar to the longer-lived strain, while extending lifespan 25–26%, whether begun before fertilization or at maturity. The short-lived lsq4 allele also conferred sensitivity to oxidative and thermal stresses, and lower male frequency (reflecting X-chromosome non-disjunction), traits reversed uniquely by rec-8 knockdown. A strain bearing the longer-lived lsq4 allele, differing from the short-lived strain at <0.3% of its genome, derived no lifespan or stress-survival benefit from rec-8 knockdown. We consider two possible explanations: high rec-8 expression may include increased “leaky” expression in mitotic cells, leading to deleterious destabilization of somatic genomes; or REC-8 may act entirely in germ-line meiotic cells to reduce aberrations such as non-disjunction, thereby blunting a stress-resistance response mediated by innate immunity. Replicative lifespan was extended 20% in haploid S. cerevisiae (BY4741) by deletion of REC8, orthologous to nematode rec-8, implying that REC8 disruption of mitotic-cell survival is widespread, exemplifying antagonistic pleiotropy (opposing effects on lifespan vs. reproduction), and/or balancing selection wherein genomic disruption increases genetic variation under harsh conditions.